Individual Health Determinants That Predict Low Risk of Transitioning to Tobacco Use During Young Adulthood: An In-Depth Examination of Race and Ethnicity. Issue 9 (16th April 2022) - Horn, Kimberly; Crandell, Ian; Patel, Minal; Rose, Shyanika W; Schillo, Barbara; Folger, Shanell; Bernat, Debra; Branstetter, Steve
Abstract: Introduction: The present study examines the contributions of individual-level health determinants on young adult tobacco use initiation to improve understanding of racial and ethnic distinctions and to inform effective tobacco prevention strategies. Methods: Using time-to-event analyses, the 10–wave (2011–2016) Truth Initiative Young Adult Cohort, a probability-based, nationally representative sample of the US young adults aged 18–34 years ( N = 7 665), provides data to examine differences in variables that influence tobacco uptake, by race and ethnicity. Results: Among Non–Hispanic White young adults, having fewer peers who smoke cigarettes is protective against any tobacco initiation, whereas hazard of tobacco initiation increases for males, having low confidence to resist smoking, and having higher proclivity for sensation seeking. Depressive and anxiety symptoms increase uptake hazard most in the Non–Hispanic All Other Races group and least among Non–Hispanic Black individuals. Among Hispanic young adults, being female and perceiving tobacco as harmful are notably protective while being male is a notable uptake hazard. Unlike other groups, higher income levels do not lower hazards among Hispanic individuals. Cannabis use and overestimating the smoking rate among peers increase hazard least among Hispanic individuals. In the Non–Hispanic All Other Races group, aging is least protective; hazard increases notably if individuals engage in regular alcohol or cannabis use. Conclusions: Tobacco prevention efforts are critical during young adulthood. Specific tobacco uptake hazard and protective factors exist by race and ethnicity and should be considered when developing selective young adult prevention, particularly among groups with the highest risk for tobacco initiation during this life stage. Implications: Rising rates of tobacco initiation among the US young adults necessitate expanded efforts to prevent tobacco use initiation and progression beyond youth. Results highlight nuanced and differential tobacco uptake hazards by race and ethnicity for late initiation and sustained non–tobacco use among young adults. The study confirms existing evidence on tobacco use patterns and contributes to new knowledge on risk and protective factors. Tobacco prevention and control interventions, including policies, tailored in more meaningful ways could reduce tobacco use disparities among those most disproportionately affected.